A Newborn in Western Nepal with Harlequin Ichthyosis: A Case Report - Rajput, Prabhat Singh (Med Phoenix, 2022)
Harlequin ichthyosis (HI) is a rare autosomal recessive congenital ichthyosis with an incidence of 1 in 300,000 live births. It is lethal in 44% of cases and the baby is usually prematurely born. These babies have thick, highly keratinized armor-like skin, which forms large diamond, trapezoid or rectangular plates separated by deep fissures. These affect the shapes of eyelids, nose, mouth and ears, and also limit movement of the arms, legs and chest. This condition is linked with a nonsense or frameshift mutation in the ABCA12 gene, which is responsible for lipid transport in the keratinocytes. This gene synthesizes a protein that transports a lipid, epidermoside, a glucosylceramide, out of stratum corneum cells in the epidermis. To our knowledge, this is the first case report on Harlequin ichthyosis from Nepal, which makes this case unique. The take away lesson from this case is that couples with consanguineous marriages should undergo screening of ABCA12 gene if they plan to conceive.